Triz as a support methodology for new product development - Dias, Ana (2019)
The author from UNIDEMI-FCT NOVA would like to thank the Faculty of Science and Technology of the New University of Lisbon (UNL) and the Portuguese Foundation for Science and Technology (FCT) through the Strategic Project no. UID/EMS/00667/2013.